Growth charts for children-Which ones to use in post Covid era? - Phadke, Mrudula; Saunik, Sujata; Nair, Rajlakshmi; Jotkar, Raju; Menon, Pramila (International Journal of Nutrition, 2023)
A practical review compares growth chart standards and references for pediatric monitoring after the COVID era. It advises on selection, interpretation, and equity considerations in diverse populations.
Keywords: Growth Charts; Pediatric Monitoring; Equity; COVID; Populations